Customization of Source Term into JRODOS Compatible XML File Format Using Visual Basic for Nuclear Accident Analysis - Hassan, S. M. T.; Khaer, M. A.; Hoq, M. A.; Chowdhury, M. T.; Rahman, M. M. (National Research and Innovation Agency, 2025)
A Visual Basic code was developed to generate an XML file in the RODOS format from the provided source term data in Microsoft Excel Spreadsheet. This XML file can be directly used in JRODOS (Java-based Real-time On-line Decision Support) platform. A simple source term model was used to check the applicability of the code. Finally, the code was successfully implemented to reproduce the JRODOS-formatted XML file for a detailed Fukushima Dai-ichi nuclear power plant accidental scenario. This code simplifies a vital analysis step, which would otherwise be very cumbersome, especially for a complex source term scenario involving many radionuclides, release intervals, and release heights of a nuclear accident.